1982
DOI: 10.1021/jm00354a020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and topical antiinflammatory activity of some steroidal [16.alpha.,17.alpha.-d]-isoxazolidines

Abstract: In each case only [ 16a,l 7a-d] isoxazolidines were isolated. The pentacyclic adducts 16-19 were active topical antiinflammatory agents in mice, with 18 being more potent than any of the standard compounds tested. The hexacyclic adduct 20 was inactive in this assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…For uses of benzopyran and isoxazolidine derivatives, see: Green et al (1982); Kashiwada et al (2001); Mullen et al (1988). For a related structure, see: Swaminathan et al (2011).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For uses of benzopyran and isoxazolidine derivatives, see: Green et al (1982); Kashiwada et al (2001); Mullen et al (1988). For a related structure, see: Swaminathan et al (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…For example, some benzopyran derivatives exhibit anti-HIV activities (Kashiwada et al, 2001). Similarly, isoxazolidine derivatives exhibit anti-fungal (Mullen et al, 1988), antiinflammatory (Green et al, 1982) and other such biological activities. In this paper we report the synthesis and crystal structure of the title compound which comprises an isoxazole ring, trans-fused with the pyran ring of the chromene moiety, a methyl benzene ring and a carbonitrile group cis-attached to the adjacent carbon atoms and a benzene ring attached to the nitrogen atom of the isoxazole ring.…”
Section: S1 Commentmentioning
confidence: 99%
“…Heating the DMF solution of 27 with KOAc effects the deacylation furnishing the desired olefins ( 28 ) (Scheme 4). 3740…”
Section: Synthesis Of Anti-inflammatory Steroidal Antedrugsmentioning
confidence: 99%
“…The valuable and diverse biological activity of molecules containing pyrrolo‐isoxazolidines, isoxazolidine, pyrrole, and pyrrolidinone moieties confers on them a high pharmacological value. Michael et al reported isoxazolidine ring fused with ring d of steroidal moieties as potential anti‐inflammatory agents and such analogs have found clinical status . Isoxazolidine derivatives also act as anti‐HIV agents .…”
Section: Introductionmentioning
confidence: 99%